2020
DOI: 10.1002/jbm.b.34698
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of programmed death‐1 decreases neointimal hyperplasia after patch angioplasty

Abstract: Neointimal hyperplasia remains an obstacle after vascular interventions. Programmed death-1 (PD-1) antibody treatment decreases tumor cell proliferation and secretion of inflammatory factors, and several antineoplastic drugs show efficacy against neointimal hyperplasia. We hypothesized that inhibition of PD-1 inhibits neointimal hyperplasia in a rat patch angioplasty model. In a rat aorta patch angioplasty model, four groups were compared: the control group without treatment, a single dose of humanized PD-1 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 55 publications
2
17
0
Order By: Relevance
“…We also showed that cells migrated and infiltrated into the decellularized fish swim bladder patch in a process similar to our previous observations that cells infiltrated into pericardial patches 23 , 38 , polyester patches 29 , decellularized human saphenous vein patches 25 and decellularized rat thoracic aortic patches 26 . Also similar to other biomaterials, there was rapid reendothelialization after patch implantation or tube interposition; there were no patch pseudoaneurysms after aortic patch angioplasty, suggesting the structural strength and biocompatibility with the arterial environment (Fig.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…We also showed that cells migrated and infiltrated into the decellularized fish swim bladder patch in a process similar to our previous observations that cells infiltrated into pericardial patches 23 , 38 , polyester patches 29 , decellularized human saphenous vein patches 25 and decellularized rat thoracic aortic patches 26 . Also similar to other biomaterials, there was rapid reendothelialization after patch implantation or tube interposition; there were no patch pseudoaneurysms after aortic patch angioplasty, suggesting the structural strength and biocompatibility with the arterial environment (Fig.…”
Section: Discussionsupporting
confidence: 88%
“…We tested the application of the decellularized swim bladder without or with rapamycin coating as patches placed into the rat aorta or the IVC 25 , 26 , 28 , 29 . At day 14, the patches were incorporated into the rat aorta and IVC; there were no aneurysms or occlusions.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Antibody or oligonucleotide infusion or viral vectors have been widely used to inhibit the signaling pathways for the prevention of neointimal hyperplasia (32)(33)(34)(35)(36). Next, we evaluated whether injury-induced neointimal hyperplasia could be reduced by blocking α9β1 signaling.…”
Section: Discussionmentioning
confidence: 99%